Darwin’s “strange inversion of reasoning” (2009)
Darwin’s theory of evolution by natural selection unifies the world of physics with the world of meaning and purpose by proposing a deeply counterintuitive ‘‘inversion of reasoning’’ (according to a 19th century critic): ‘‘to make a perfect and beautiful machine, it is not requisite to know how to make it’’ (MacKenzie 1868). Turing proposed a similar inversion: to be a perfect and beautiful computing machine, it is not requisite to know what arithmetic is. Together, these ideas help to explain how we human intelligences came to be able to discern the reasons for all of the adaptations of life, including our own.